Summer days - Mallery, Susan (Don Mills, Ont. : HQN, 2012)
"Locked in an unexpected land dispute, Rafe Stryker is trapped in the one place he vowed never to return to--the Castle Ranch in Fool's Gold, California. He made millions facing ruthless adversaries in the boardroom, but nothing could've prepared him to go head-to-head against stubborn, beautiful Heidi Simpson. No one is more surprised than Rafe to discover that he's finding Heidi--and life as a cowboy--much more compelling than he wants to admit. For Heidi, the Castle Ranch is the home she's always wanted. After a life on the road, the vivacious blonde has finally put down roots. She won't give that up without a fight, not even for a man whose late night kisses make her yearn to be a little less wholesome. As the two turn from passionate adversaries to passionate, period, they'll discover that summer love can last a lifetime"--Cover, p. [4].
Keywords: Ranch life -- California -- Fiction; Cowboys -- Fiction; California -- Fiction; Love stories